Astrovirus Outbreak in an Animal Shelter Associated With Feline Vomiting - Li, Yanpeng; Gordon, Emilia; Idle, Amanda; Hui, Alvin; Chan, Roxanne; Seguin, M. Alexis; Delwart, Eric (Frontiers in Veterinary Science, 2021)
An outbreak of cat vomiting was observed in an animal shelter. Testing for known enteric feline pathogens did not identify a causative agent. Viral metagenomics on four mini-pools of feces from cases and controls housed in the same area revealed the presence of feline astrovirus in all pools. Also found with fewer reads in one pool each were rotavirus I, carnivore bocaparvovirus 3, norovirus (NoV) GVI, and a novel dependovirus. The genome of the highly prevalent astrovirus was sequenced and classified into mamastrovirus species 2, also known as feline astrovirus. Real time RT-PCR on longitudinally acquired fecal samples from 11 sick cases showed 10 (91%) to be shedding astrovirus for as long as 19 days. Affected cats were sick for an average of 9.8 days with a median of 2.5 days (range: 1-31 days). Unaffected control cats housed in the same areas during the outbreak showed 5/9 (56%) to also be shedding astrovirus. Feline fecal samples collected from the same animal shelter approximately one year before (n=8) and after (n=10) showed none to be shedding astrovirus, indicating that this virus was temporarily associated with the vomiting outbreak and is not part of the commensal virome for cats in this shelter. Together with the absence of highly prevalent known pathogens our results support a role for feline astrovirus infection, as well as significant asymptomatic shedding, in an outbreak of contagious feline vomiting.